Transition to Market : Studies in Fiscal Reform. (International Monetary Fund, 1993)
The IMF has been a major participant in the challenge of transforming many African, Asian, and European countries from centrally planned to market economies. The authors of this book, mainly staff members of the IMF, have distilled their firsthand experience with fiscal reform in transition economies into 15 case studies of these countries. In doing so they analyze issues of privatization, fiscal federalism, social safety nets, and the net worth of the Soviet Union. The editor of the volume is Vito Tanzi, Director of the IMF's Fiscal Affairs Department.